2005
DOI: 10.1038/nm1258
|View full text |Cite
|
Sign up to set email alerts
|

Live attenuated recombinant vaccine protects nonhuman primates against Ebola and Marburg viruses

Abstract: Vaccines and therapies are urgently needed to address public health needs stemming from emerging pathogens and biological threat agents such as the filoviruses Ebola virus (EBOV) and Marburg virus (MARV). Ebola virus (EBOV) and Marburg virus (MARV) of the virus familyFiloviridae are emerging and reemerging pathogens that cause hemorrhagic fever with high mortality rates in humans and nonhuman primates 1-3 . The public health concern about filoviruses has increased in recent years as a result of increased aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
561
6
14

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 621 publications
(608 citation statements)
references
References 23 publications
27
561
6
14
Order By: Relevance
“…Nucleoprotein alone provided incomplete protection in monkeys infected with MARV, whereas viral glycoprotein by itself (or admixed with nucleoprotein) prevented illness and death in six out of six infected animals 4 . Similarly, the first successes in protecting non-human primates against ZEBOV were with a vaccine containing glycoprotein; subsequent studies showed glycoprotein by itself to be sufficient 64,65 , and there are no published data to indicate that there are any other proteins capable of protecting non-human primates against ZEBOV in the absence of glycoprotein.…”
Section: Anergymentioning
confidence: 99%
See 2 more Smart Citations
“…Nucleoprotein alone provided incomplete protection in monkeys infected with MARV, whereas viral glycoprotein by itself (or admixed with nucleoprotein) prevented illness and death in six out of six infected animals 4 . Similarly, the first successes in protecting non-human primates against ZEBOV were with a vaccine containing glycoprotein; subsequent studies showed glycoprotein by itself to be sufficient 64,65 , and there are no published data to indicate that there are any other proteins capable of protecting non-human primates against ZEBOV in the absence of glycoprotein.…”
Section: Anergymentioning
confidence: 99%
“…It has been confounding to some researchers that neutralization of filoviruses by antibodies -as measured by a reduction in viral infectivity after admixture with antibodies -has proved to be a completely unreliable in vitro predictor of antibody or vaccine effectiveness 4,64,70,76 . Others researchers point to a rich history of antibodies shown to protect in ways other than what is popularly understood as neutralization 77 .…”
Section: Humoral Immunity Against Filovirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…When challenged intramuscularly with a lethal dose of 1,000 PFU of EBOV 28 days after vaccination, animals were completely protected, with no disease signs and no challenge virus viremia detectable. 10 Vaccination with VSV-EBOV also protected cynomolgus macaques from lethal challenge via the aerosol route. 11 …”
Section: Introductionmentioning
confidence: 99%
“…10 , 13 Importantly, it was shown that vaccination of cynomolgus macaques with a VSV-EBOV vaccine expressing the GP from the EBOV-Kikwit strain, isolated during the 1995 EBOV outbreak in Kikwit, Democratic Republic of the Congo, 21 that was subsequently used in clinical trials resulted in complete protection from lethal challenge with the EBOV-Makona strain isolated during the West African EBOV epidemic. 20 Thus, the currently available VSV-EBOV vaccine will likely be protective in future EBOV outbreaks.…”
Section: Introductionmentioning
confidence: 99%